Expectation Confirmation Theory on Video Games Among Players: AAA Studios vs Indie Developers - Tony Wibowo; Davin Lim; Tony Tan (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2026)
This research investigates the comparison between AAA and indie games among players in Southeast Asia, utilizing Expectation Confirmation Theory (ECT) and the DeLone & McLean Information Systems Success Model as theoretical frameworks. The study's primary objective is to gain an understanding of player preferences, expectations, and satisfaction levels for both AAA and indie games in this rapidly expanding market. Findings reveal that a majority of players (76.4%) exhibit balanced preferences, with slight inclinations towards either AAA or indie games, suggesting an appreciation for the unique qualities offered by both game types. AAA games were notably recognized for their technical optimization and superior system quality, while indie games excelled in creativity, emotional engagement, and meeting player expectations. These insights provide guidance for game developers to understand and cater to player expectations and preferences in the Southeast Asian market. The research highlights opportunities for developers to strike a balance between technical polish and innovative gameplay, while also emphasizing the importance of community engagement. This study makes a contribution to the limited existing research comparing AAA and indie games, particularly within the context of the Southeast Asian market.